Mechanisms for self‐templating design of micro/nanostructures toward efficient energy storage. Issue 5 (31st May 2022) - Hui, Zengyu; An, Jianing; Zhou, Jinyuan; Huang, Wei; Sun, Gengzhi
Abstract: The ever‐growing demand in modern power systems calls for the innovation in electrochemical energy storage devices so as to achieve both supercapacitor‐like high power density and battery‐like high energy density. Rational design of the micro/nanostructures of energy storage materials offers a pathway to finely tailor their electrochemical properties thereby enabling significant improvements in device performances and enormous strategies have been developed for synthesizing hierarchically structured active materials. Among all strategies, the direct conversion of precursor templates into target micro/nanostructures through physical and/or chemical processes is facile, controllable, and scalable. Yet the mechanistic understanding of the self‐templating method is lacking and the synthetic versatility for constructing complex architectures is inadequately demonstrated. This review starts with the introduction of five main self‐templating synthetic mechanisms and the corresponding constructed hierarchical micro/nanostructures. Subsequently, the structural merits provided by the well‐defined architectures for energy storage are elaborately discussed. At last, a summary of current challenges and future development of the self‐templating method for synthesizing high‐performance electrode materials is also presented. Abstract : The micro/nanostructure design via self‐templating method offers a viable way to significantly improve the electrochemical performances of functional materials. This review introduces five main self‐templating mechanisms and compares the merits of different micro/nanostructures for energy storage. Furthermore, a summary of current challenges and the prospect of self‐templating strategy for constructing high‐performance electrode materials are also presented.